The Relationship Between Burnout and Violence Tendencies of Caregivers of Patients with Schizophrenia - Ömer Faruk Cantekin; İpen İlknur Ünlü (Universitas Negeri Semarang (UNNES) in cooperation with the Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2024)
The importance of family has increased with the adoption of the community-based approach in the treatment of patients with schizophrenia and returning them to their social environments. Schizophrenia is a chronic mental illness, that affects not only the individual but also the family’s life because 10% of suffered individuals with illness need such long-term care and needed support from their families. This study aims to examine the relationship between burnout and violent tendencies among caregivers of schizophrenia patients. The study was a correlational and cross-sectional survey and followedquantitative methodology. The population consisted of 60 caregivers who took primary responsibility and spent the most time with patients diagnosed with “schizophrenia” according to DSM-V-TR diagnostic criteria, who were registered in a health center. In line with the purpose of the research, data collection tools are the Personal Information Form, Maslach Burnout Scale, and Violence Tendency Scale. The study found that there was a positive significant relationship between burnout and violence tendency among caregivers (r=0.539; p=0.000<0.05). In other words, burnout of caregivers increases violence tendency. In addition, the sub-dimensions of burnout significantly affected thepropensity to violence (F=8,657; p=0.000<0.05). The severity of illness in schizophrenia patients impairs their caregivers’ mental health. Families caring for persons with schizophrenia have difficulty tolerating them if the families have a feeling of burnout. Dissemination of psychosocial practices among caregivers of schizophrenia patients in adjunct to treatment will help families reduce their level of burnout and depression.